Autentikasi User Dengan Metode Single Sign-On Berbasis Windows Active Directory Pada PT. XYZ - Kemas, Kemas Ocha Khairi Saputra; Supriyatna, Agiska Ria; Putra, Septafiansyah Dwi (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2024)
To connect to the company network, a WPA2-PSK-based security system is in place, requiring users to input the company Wi-Fi password. One of the issues that arises is the difficulty in identifying the status of users attempting to access the network. Apart from security concerns regarding the network, the use of this security key allows non-employees to connect to the network using personal devices. As a solution to enhance the existing authentication system, security systems like RADIUS can be utilized. This system operates to mitigate threats to the network security. The process undertaken through the implementation of this NDLC method commences with identifying and designing network security authentication, progressing through the implementation phase until the design can be regularly utilized. With the introduction of a user authentication system employing a single sign-on method based on Windows Active Directory at XYZ Inc., users will find it easier to connect to the wireless network. With WPA2-Enterprise, access to the network will be restricted.